The Pleasures of Metamorphosis : Japanese and English Fairy-Tale Transformations of "The Little Mermaid" - Fraser, Lucy (Book collections on Project MUSE., 2017)
Analysis of the mermaid in Japanese and English fairy tales through the framework of pleasure.